Application of Interpretative Structural Modelling (ISM) In The Development of Barokah Chips on The Scale of The Household Industry In Unaaha District, Konawe Regency - Heriyanto Heriyanto; Sarinah Sarinah; Rosmawaty Rosmawaty (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to determine the planning of implementing strategic policies in the development of Barokah chips. The method used in this research is Interpretative Structural Modeling (ISM) with this approach can determine the relationship between elements in the system. The results of this study are the factors are divided into four levels and are included in the autonomous, dependent, linkage, and independent sectors. The key factors that influence are all elements of actor factors/elements, constraints, needs and goals, one of which plays an important role in actor/stakeholder elements, namely farmers, traders, consumers, cooperatives and UMKM offices, financial institutions and the industry and trade offices as well as the consistency percentage results obtained. obtained from each element.